Effect of Glucose Insulin Potassium Infusion on Myocardial Injury and Endothelin-1 Levels in Chronic Ischemic Heart Failure - Yazıcı, M.; Demircan, S.; Aksakal, E.; Soylu, K.; Şahin, M.; Saǧkan, O. (My University, 2004)
In this study, the effects of long term glucose insulin potassium (GIK) infusion on myocardial injury and endothelin-1 levels in patients with chronic ischemic heart failure were assessed. 56 patients with NYHA functional class III-IV chronic ischemic heart failure were included who had past history of myocardial infarction (> 6 months) and obstructive coronary artery disease determined by angiography. In addition to the standard therapy administered, GIK infusion (30% 500 cc glucose + 300 U insulin + 60 mEq KCl) for 8 hours every day during 5 days was given for the randomly selected 35 patients (Group A). Those with standard treatment (21 patients, Group B) served as a control group. Echocardiographic examination as well as measurement of ET-1 and cardiac troponin-I (cTn-I) levels from venous blood samples were carried out before and after therapy in both groups. There was no significant difference in blood glucose and K+ levels during follow-up and GIK infusion. Arrhythmia and hemodynamic change were not observed. Plasma ET-1 levels were similar in both groups before treatment (Group A 3.31±0.42 pg/ml and Group B 3.36±0.53 pg/ml, p>0.05). A significant decrease in plasma ET-1 levels of both groups was noted after treatment compared to pretreatment levels (Group A 2.02±0.33 pg/ml, p<0.0001 and Group B 3.12±0.61 pg/ml, p<0.01). Decrease in ET-1 levels were more significant in the GIK group (p<0.0001). Left ventricular ejection fractions after treatment revealed a significant increase in the GIK group (p<0.001). The decrease in cTn-I levels after treatment was also significantly more prominent in the GIK group (p<0.001). We concluded that a positive effect existed of long-term GIK infusion on myocardial injury and ET-1 levels, accepted as one of hemodynamic parameters of heart failure. Long-term GIK infusion may have positive contribution to clinical progression of patients with chronic ischemic heart failure, in addition to standard treatment.
Kronik İskemik Kalp Yetersizliğinde Glukoz-İnsülin-Potasyum İnfüzyonunun Endotelin-1 Düzeyleri ve Miyokard Hasarına Etkisi
Keywords: Chronic Heart Failure; Endothelin-1; Glucose-Insulin-Potassium Infusion; Myocardial Injury